Igniting children’s enthusiasm for microbes with an origami paper microscope - Joshua Gardner; Cynthia Perry; Jorge Cervantes (Journal of Microbiology & Biology Education, 2024)
ABSTRACTThe COVID-19 pandemic has underscored the urgent need for microbiology literacy in society. Microbiology knowledge, and its dissemination, can help inform and increase the objectivity of important decisions, such as treatment or vaccination. A microbiology learning experience titled “What you can’t see can hurt you” was delivered as part of a larger outreach event where children were exposed to various aspects of medicine and health care fields. The activity involved an introduction to and a discussion of bacteria of clinical importance and the use of a smartphone-attachable paper-based foldable microscope. To explore the impact of this activity on participants’ interest in science and microbiology, a pre- and post-activity survey of five questions on an emoji-based Likert scale was completed by the participants. A statistically significant increase in their interest in microbes and where to find them, as well as in microscopy, was observed after the event. Making microbes visible to children and allowing them to capture images of microbes exposes them directly and personally to microscopy and microbiology. An affordable low-cost paper-based microscope can become an alternative approach to teaching and learning to deliver clinical microbiology information to a wide audience range.